2014
DOI: 10.1007/s13277-014-2662-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased PTOV1 expression is related to poor prognosis in epithelial ovarian cancer

Abstract: Altered expression of prostate tumor overexpressed-1 (PTOV1) is observed in various types of human cancers. However, the role of PTOV1 in epithelial ovarian cancer (EOC) remains unclear. PTOV1 messenger (m)RNA expression in EOC patients was evaluated by quantitative real-time PCR (qRT-PCR). PTOV1 protein expression was also analyzed in archived paraffin-embedded EOC tissues using immunohistochemistry (IHC), and its association with overall survival of patients was analyzed by statistical analysis. Results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…A strong nuclear staining was more frequently found in the T3 or T4 stage and metastatic cancer cells; from the clinical data, we also found a correlation between PTOV1 overexpression and ESCC clinical progression. Similar to other findings, 12,13,15 PTOV1 overexpression had a strong relationship with the tumor size and T staging. Moreover, IHC staining showed that the intensity of PTOV1 expression in the ESCC tissues increased with progressing clinical stage and lymph node involvement, and all these collectively indicated that the elevated expression of PTOV1 lead to a more aggressive character.…”
Section: Discussionsupporting
confidence: 89%
“…A strong nuclear staining was more frequently found in the T3 or T4 stage and metastatic cancer cells; from the clinical data, we also found a correlation between PTOV1 overexpression and ESCC clinical progression. Similar to other findings, 12,13,15 PTOV1 overexpression had a strong relationship with the tumor size and T staging. Moreover, IHC staining showed that the intensity of PTOV1 expression in the ESCC tissues increased with progressing clinical stage and lymph node involvement, and all these collectively indicated that the elevated expression of PTOV1 lead to a more aggressive character.…”
Section: Discussionsupporting
confidence: 89%
“…Consistently, this study also showed that PTOV1 increases the proportion of SP cells, which can exclude the DNA-binding dye Hoechst 33342, suggesting that PTOV1 may enhance the chemoresistance of breast cancer cells. Although numerous studies have elucidated the significance of PTOV1 in a variety of tumours [3,21,33,34], this is the first report of a role for PTOV1 in the stemness of cancer cells. Thus, our findings not only reveal a novel mechanism for the maintenance of CSCs in breast cancer but also represent a novel target for restraining the CSC population in breast cancer.…”
Section: Discussionmentioning
confidence: 81%
“…PTOV1 was initially identified in prostate cancer, but it has recently been reported to enhance the population of cancer stem cells via the activation of Wnt/β-catenin signaling in breast cancer (15). PTOV1 is also a key player in tumor progression and is associated with a poor prognosis in laryngeal squamous cell carcinoma, urothelial carcinoma, and ovarian cancer (1618). In addition to the oncogenic roles of its sense transcripts, our findings strongly suggest that antisense PTOV1-AS1 is also involved in cancer proliferation via miR-1207-5p.…”
Section: Discussionmentioning
confidence: 99%